2008
DOI: 10.1021/jf8014206
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Chinese Propolis and Its Component, Chrysin, against Neuronal Cell Death via Inhibition of Mitochondrial Apoptosis Pathway in SH-SY5Y Cells

Abstract: Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of neurodegenerative and ischemic disorders. The purpose of this study was to evaluate the effects of Chinese propolis and its constituents [chrysin, galangin, pinocembrin, caffeic acid, and caffeic acid phenethyl ester (CAPE)] against tunicamycin-induced neuronal cell death in SH-SY5Y cells. Both Chinese propolis and chrysin concentration-dependently inhibited such cell death, the tunicamycin-induced activation of caspase-3, and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…19) Furthermore, chrysin also has the protective effect against endoplasmic stress-induced neuronal cell death. 20) These findings indicate the possibility that luteolin has the protective effects against endoplasmic reticulum stress-induced depression and/or cell damage. In the present study, we investigated the effects of luteolin against endoplasmic reticulum stress-induced neuronal cell death in vitro and depression in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…19) Furthermore, chrysin also has the protective effect against endoplasmic stress-induced neuronal cell death. 20) These findings indicate the possibility that luteolin has the protective effects against endoplasmic reticulum stress-induced depression and/or cell damage. In the present study, we investigated the effects of luteolin against endoplasmic reticulum stress-induced neuronal cell death in vitro and depression in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, it has been demonstrated that BFA and TUN promote the translocation of cytochrome c from the mitochondrial matrix to the cytosol (20,21). In light of this, we further investigated the caspase-2 activity, which promotes cytosolic cleavage of Bid to tBid, acting upstream of cytochrome c release and being involved in ER stress-mediated death (22)(23)(24), and caspase-9 activity, which is involved in the cell death signals propagation triggered by mitochondria (25).…”
Section: Bfa and Tun-induced Stress Activates Er-and Mitochondria-depmentioning
confidence: 94%
“…[36] Chinese propolis and chrysin inhibited staurosporine-induced cell death. These findings indicate that the inhibitory effects of Chinese propolis against neuronal cell death induced by endoplasmic reticulum stress or staurosporine may be exerted primarily by chrysin.…”
Section: Possible Mechanism Of Action Of Propolis and Its Compounds Ementioning
confidence: 95%
“…HT-29, A549, HEp-2, RAW 264.7, Vero Seda et al [33] Ethanolic extract (Turkey) MCF-7 Valente et al [13] Methanolic extract (Portugal) A498 Huang et al [34] Propolin G (Taiwan) C6, DBTRG-05MG Diaz-Carballo et al [35] Mucronulatol (Caribbean) HCT8, MDR1-/ MDR3+ Izuta et al [36] Chrysin, galangin, pinocembrin, caffeic acid, caffeic acid phenethyl ester (China)…”
Section: Flavonoidsmentioning
confidence: 99%